Faktor-Faktor Yang Berkaitan Dengan Status Gizi Balita Di Masa Pandemi Tinjauan Literatur Sistematik - Dian Ayubi; Raya Faiha Calista (NERSMID : Jurnal Keperawatan dan Kebidanan, 2023)
Nutritional status is an important factor in the process of optimizing growth and development, especially in toddlers. At this time, there is an optimization of the process of growth and development which is very fast which is often referred to as the "golden age period". Malnutrition in toddlers, especially stunting, in the first 1000 days of life can have an impact that lasts a lifetime. The multisectoral crisis during the Covid-19 pandemic was a factor that was closely related to the nutritional status of toddlers during the pandemic. Method: In this study the method used was a systematic literature review study using a systematic flow based on PRISMA. Searches were performed on 8 databases published 2020 - 2022 with predefined keywords and search restrictions. Results: This literature review obtained 865 publications through Elsevier, Science Direct, ProQuest, Google Scholar, PubMed and Scopus. A total of 13 articles were obtained that were suitable for analysis related to the impact of the COVID-19 pandemic on toddler nutrition. The methods used in this study are cohort, modeling, cross sectional and descriptive. There are 13 study themes related to impact and factors related to the nutritional status of toddlers during the Covid-19 pandemic. Conclusion: The COVID-19 pandemic has created a crisis in various sectors related to the nutritional status of toddlers. The main factors related to the nutritional status of children under five are parenting behavior and parenting, especially changes in food parenting practices and eating habits due to social restrictions. So that positive parenting is the key to creating family resilience during the pandemic.